Application trends of the systemic paradigm in pharmaceutical research - T. V. Mahanova; N. О. Tkachenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Pharmacists use systematic knowledge to study the regularities of complex, multilevel systems with a considerable number of variable, feedback connections between them in order to find or make rational management decisions. However, the level and direction of application of the system paradigm of knowledge in pharmacy remain to the end do not determine.